2016
DOI: 10.1038/srep22279
|View full text |Cite
|
Sign up to set email alerts
|

The fetal ovary exhibits temporal sensitivity to a ‘real-life’ mixture of environmental chemicals

Abstract: The development of fetal ovarian follicles is a critical determinant of adult female reproductive competence. Prolonged exposure to environmental chemicals (ECs) can perturb this process with detrimental consequences for offspring. Here we report on the exposure of pregnant ewes to an environmental mixture of ECs derived from pastures fertilized with sewage sludge (biosolids): a common global agricultural practice. Exposure of pregnant ewes to ECs over 80 day periods during early, mid or late gestation reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…By exposing pregnant ewes during early, mid, late or the whole gestation period to a mixture of environmental chemicals, including EDCs, disrupted fetal folliculogenesis was induced in all exposure groups, likely due to effects on follicle assembly. At the molecular level, however, the most pronounced changes to gene and protein expression was observed in fetuses having been exposed during mid-late gestation 88 .…”
Section: Chemical Exposure Affects Follicle Assemblymentioning
confidence: 98%
See 2 more Smart Citations
“…By exposing pregnant ewes during early, mid, late or the whole gestation period to a mixture of environmental chemicals, including EDCs, disrupted fetal folliculogenesis was induced in all exposure groups, likely due to effects on follicle assembly. At the molecular level, however, the most pronounced changes to gene and protein expression was observed in fetuses having been exposed during mid-late gestation 88 .…”
Section: Chemical Exposure Affects Follicle Assemblymentioning
confidence: 98%
“…What complicates the picture even further, is that humans are continuously exposed to a large number of chemicals at any given time 119 , whereas controlled animal experiments typically involves the exposure of single chemicals during specific time windows. To overcome this hurdle, a series of studies were conducted exposing sheep on pastures before and during pregnancy to a mixture of environmental chemicals 88,120,121 . The studies focusing on female fetuses found that constant maternal exposure to a low-concentration mixture of chemicals can disrupt ovary development 120 , and that exposure during mid and late gestation was most detrimental 88 .…”
Section: Human Versus Animal Datamentioning
confidence: 99%
See 1 more Smart Citation
“…5,238,[251][252][253][254][255][256] This has led to a considerable literature of the effects on animals and their offspring that graze on pastureland amended with sludge containing multiple EDs. 95,[257][258][259][260][261][262][263][264][265][266][267] Since these studies mostly concern multi-ED exposures, we consider this area outside the scope of the current mini-reviews. Sludge is the primary source of 1a soil contamination.…”
Section: Mini-review Of Bpa Occurrencesmentioning
confidence: 99%
“…Owing to their complexity, environmental mixtures are virtually impossible to reproduce artificially, thus enabling investigations into the effect of the "whole mixture" exposure on biological functions (Lea et al, 2016). Sewage sludge fertilizer containing readily detectable levels of EDs has been used to investigate the effect of a "real-life" mixture on the ovarian (Lea et al, 2016), testicular (Paul et al, 2005), thyroid gland (Hombach-Klonisch et al, 2013), and hypothalamopituitary axis (Bellingham et al, 2010) development. Exposure to wastewater effluents, which also represent a source of various EDs, is associated with a range of reproductive effects, particularly in fish, such as lowered hormone levels (Folmar et al, 1996) and reduced gamete production and fertilization capabilities (Jobling et al, 2002).…”
Section: Introductionmentioning
confidence: 99%